ByzRev 08.2026.032: Nikoloz Aleksidze – Ekaterine Gedevanishvili (eds.), Warrior Saints in Medieval Georgian Art: Tbilisi: Giorgi Chubinashvili National Research Centre for Georgian Art History and Heritage Preservation 2025 - Badamo, Heather (The Byzantine Review, 2026)
Nikoloz Aleksidze – Ekaterine Gedevanishvili (eds.), Warrior Saints in Medieval Georgian Art. Tbilisi: Giorgi Chubinashvili National Research Centre for Georgian Art History and Heritage Preservation 2025. 460 pp., 370 ill. – ISBN 978-9941-8-7414-7 open access: https://rustaveli.org.ge/res/docs/e9416a58f59b2fccf8ca738dd8ff5b00b4469c13.pdf